P5 Project Theme: The Voice of Democracy As Cross-Curricular Political Education (Study at SMA Dek Padang) - Pratama, Mayoga; Rafni, Al; Suryanef, Suryanef; Indrawadi, Junaidi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
is study examines the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme Voice of Democracy at SMA DEK Padang as a vehicle for cross-curricular political education. Political education is considered crucial for shaping young citizens who are knowledgeable, critical, and participatory in democratic life. However, it often remains limited to cognitive aspects, neglecting democratic practices and participatory skills. Using a qualitative descriptive approach, this research collected data through interviews, participatory observation, and questionnaires involving teachers, student council administrators, and eleventh-grade students. The findings reveal that the Voice of Democracy project provided students with meaningful experiences in understanding and practicing democracy through activities such as election simulations, open debates, campaign design, and collaborative decision-making. These activities successfully integrated multiple subjects, including Civic Education, Indonesian Language, and Visual Communication Design, enriching students’ political literacy, communication, and creativity. Moreover, the project fostered deliberative participation, negotiation skills, and political efficacy, as students not only learned concepts theoretically but also experienced democratic processes in practice. The reflection stage enabled critical evaluation, encouraging students to internalize values of justice, tolerance, and responsibility. Despite challenges such as uneven student engagement and cross-subject coordination, the project demonstrated significant potential in developing democratic attitudes and participatory skills. Ultimately, this study highlights the strategic role of schools as agents of political education in the Merdeka Curriculum era, showing how project-based learning can transform abstract democratic principles into lived experiences for students.